Cascading multispectral polarization cages - Yan Li; Muhammad Afnan Ansari; Hammad Ahmed; Facheng Zhong; Xianzhong Chen (npj Nanophotonics)
Abstract 3D optical polarization structures are complex structured beams and possess exotic optical properties. Multispectral information can dramatically increase information capacity. To meet the requirement of the prevailing trend towards integration and compactness, there is an urgent need to develop ultrathin elements capable of simultaneously controlling polarization and color in three-dimensional (3D) space. Cascading multiple 3D polarization structures with different colors has not been reported due to the fundamental challenge. We use a geometric metasurface to generate cascaded polarization cages and dynamically modulate their polarization profiles. A red polarization cage is embedded in the second cyan polarization cage. Different polarization cages are generated by controlling the incident wavelength, while their polarization distributions are modulated by controlling the incident linear polarization. This approach integrates 3D polarization generation, multiple colors, and cascading technology, providing extra degrees of freedom for metasurface design and enabling small-volume polarization systems for engineering 3D vector beams.